2006
DOI: 10.1051/0004-6361:20053609
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent model of a 22 GHz water maser in a dusty environment near late-type stars

Abstract: We study the conditions for operation of the 22 GHz ortho-water maser in a dusty medium near late-type stars. The main physical processes, such as exchange of energy between dust and gas in the radiation field of a star, radiative cooling by water molecules and pumping of water masers are described self-consistently. We show that the presence of dust grains of various types (or of one type with size distribution) strongly affects the maser action. The pumping mechanism based on the presence of the dust of diff… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 35 publications
2
6
0
Order By: Relevance
“…According to our calculations, the gain in the 22.2-GHz maser line is less than 10 −14 cm −1 for such densities. Note that Babkovskaia and Poutanen (2006) showed that the pumping of 22.2-GHz maser in the circumstellar envelopes is more efficient at H 2 number densities 10 7 -10 8 cm −3 and high H 2 O relative abundances, which agrees with our results.…”
Section: Discussionsupporting
confidence: 92%
“…According to our calculations, the gain in the 22.2-GHz maser line is less than 10 −14 cm −1 for such densities. Note that Babkovskaia and Poutanen (2006) showed that the pumping of 22.2-GHz maser in the circumstellar envelopes is more efficient at H 2 number densities 10 7 -10 8 cm −3 and high H 2 O relative abundances, which agrees with our results.…”
Section: Discussionsupporting
confidence: 92%
“…With water closer to the star, it is less susceptible to external forces like interstellar UV radiation that convert water to OH. Also unlike 1612-MHz OH maser emission, water masers are pumped by both radiation and collisions with H2 molecules (Babkovskaia & Poutanen 2006). It is possible that the relative strengths of the maser pumping mechanisms may differ at lower metallicity.…”
Section: Oh Abundancementioning
confidence: 99%
“…The gas and dust temperatures in the cloud depend on cooling and heating processes such as gasdust collisions, radiative cooling and heating by starlight. We use the calculation results from [10,11]. The dust and gas temperatures are taken to be equal 400 K and 600 K, respectively.…”
Section: Physical Modelmentioning
confidence: 99%